2011
DOI: 10.1152/ajpregu.00244.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic dietary salt loading on the renin angiotensin and adrenergic systems of rainbow trout (Oncorhynchus mykiss)

Abstract: NJ, Montpetit C. Effects of chronic dietary salt loading on the renin angiotensin and adrenergic systems of rainbow trout (Oncorhynchus mykiss). Am J Physiol Regul Integr Comp Physiol 301: R811-R821, 2011. First published June 22, 2011 doi:10.1152/ajpregu.00244.2011.-Previous studies have demonstrated that chronic dietary salt loading causes hypertension and a decreased sensitivity of the systemic vasculature to ␣-adrenergic stimulation and other hypertensive stimuli (e.g. hypercapnia) in rainbow trout (Onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…It is wellknown that a variety of cardiovascular risk factors are closely associated with Ang II (21)(22)(23). The ability of Ang II to elevate blood pressure is 10∼40 times powerful than adrenaline (24). Ang II raises blood pressure through multiple factors, mainly through stimulating zona glomerulosa of the adrenal gland, promoting aldosterone secretion and sodium-water retention (20,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…It is wellknown that a variety of cardiovascular risk factors are closely associated with Ang II (21)(22)(23). The ability of Ang II to elevate blood pressure is 10∼40 times powerful than adrenaline (24). Ang II raises blood pressure through multiple factors, mainly through stimulating zona glomerulosa of the adrenal gland, promoting aldosterone secretion and sodium-water retention (20,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In teleost fish, catecholamine secretion is stimulated via acetylcholine release at the terminal end of nerve fibres of chromaffin cells located in the posterior cardinal vein and the head kidney (Nilsson et al, 1976; Porteus et al, 2012). Hypoxia (Porteus et al, 2012), hypotension (Perry et al, 2011; Sandblom et al, 2010), air exposure (Lennox et al, 2016; Sopinka et al, 2016), metabolic acidosis (Wood, 1991, 1994), and changes in water temperature (Currie et al, 2013) can lead to increased levels of circulating catecholamines. While sustained aerobic exercise is not correlated with changes in circulating catecholamine levels (Butler et al, 1986), increases have been observed following burst swimming exercise of fish (Primmett et al, 1986).…”
Section: Potential Links Between Exhaustion Ion Regulation Osmoregula...mentioning
confidence: 99%
“…Hypoxia (Porteus et al, 2012), hypotension (Perry et al, 2011;Sandblom et al, 2010), air exposure (Lennox et al, 2016;Sopinka et al, 2016), metabolic acidosis (Wood, 1991(Wood, , 1994, and changes in water temperature (Currie et al, 2013) can lead to increased levels of circulating catecholamines. While sustained aerobic exercise is not correlated with changes in circulating catecholamine levels (Butler et al, 1986), increases have been observed following burst swimming exercise of fish (Primmett et al, 1986).…”
Section: P Otential Link S B E T Ween E Xhaus Tion Ion Reg Ul Ation ...mentioning
confidence: 99%
“…In teleost fish, catecholamine secretion is stimulated via acetylcholine (ACh) release at the terminal end of nerve fibres of chromaffin cells located in the posterior cardinal vein and the head kidney (Nilsson et al 1976;Porteus et al 2012). Hypoxia (Porteus et al 2012), hypotension (Sandblom et al 2010;Perry et al 2011), air exposure (Lennox et al 2016;Sopinka et al 2016), metabolic acidosis (Wood 1991(Wood , 1994 and changes in water temperature (Currie et al 2013) can lead to increased levels of circulating catecholamines. While sustained aerobic exercise is not correlated with changes in circulating catecholamine levels (Butler et al 1986), increases have been observed following burst swimming exercise in fish (Primmett et al 1986).…”
Section: Potential Links Between Exhaustion Ion Regulation Osmoregula...mentioning
confidence: 99%